Pedagogical Strategies for Gross and Fine Motor Skills Learning Through Physical Education: Intervention in Students with Hearing Impairment - Paulina Yesica OCHOA MARTÍNEZ (Revista Brasileira de Educação Especial, 2020)
ABSTRACT: The objective of this study was to evaluate the effect of a program that used pedagogical strategies for gross and fine motor skills learning through Physical Education in students with hearing impairment. Fifteen students diagnosed with hearing impairment, with 7.7 ± .3 years old (men n = 9 and women n = 6), took part in a five-month program of 40 Physical Education sessions with pedagogical strategies for gross and fine motor skills learning, in which they communicated through the Mexican Sign Language. The Battelle Developmental Inventory was utilized before and after the program to measure tests of body coordination, locomotion, fine motor skills and perceptual ability, which determine gross and fine motor skills scores. Statistical analysis was performed using the student’s t-test for related samples, reporting significant differences in the gross motor skills score (p = .001) and fine motor skills score (p = .001) before and after the intervention. The percentage change was of 21.1 Δ% and 19.2 Δ% respectively. Participation for five months in a Physical Education program positively influences gross and fine motor skills coordination in students with hearing impairment.